The impact of exterior finish vapour resistance on the moisture state of building walls - Šadauskienė, Jolanta; Monstvilas, Edmundas; Stankevičius, Vytautas (Technological and Economic Development of Economy, 2007)
At present, when the building walls covered with a painted thin render are insulated by the mineral wool slabs from outside, the defects caused by the condensed moisture accumulated in the envelopes become more and more frequent. Water vapour permeability of the exterior finish (ie the paint), if compared with the water vapour permeability of the mineral wool slab, is rather small. That is why the paint coating may become the barrier for the water vapour diffusion and thus create favourable conditions for moisture accumulation in the exterior layers of the envelope during cold seasons. As a rule, to eliminate the defects, the exterior surface is repainted on the former paint coating because the render is thin and mechanically easily damaged. Repainting the thin render surface causes the following: 1) an increase of the exterior coating's vapour resistance; 2) a growth of the condensation intensity in the envelope exterior layers during the of moisture accumulation; 3) a decrease of the durability of the render‐paint system. The restrictions for the envelope exterior layer sd have already been recommended to employ in the European Union. Since moisture accumulation inside the wall is determined by the local climate, it is important to find out whether the recommendations concerning the given sd value might be applied for the exterior layers of the building walls in Lithuania. To find it out, the calculations of the envelope state and laboratory experiments have been carried out. The paper aims at the analysis of the impact of vapour permeability and its properties in the exterior layers of the wall on the envelope moisture state. It has been determined that the increase of the sd value is disproportionate to the number of the paint layers or the thickness of the paint coating. It has also been determined that the increase of the sd value forms the pre‐conditions for the increased moisture amount under service conditions caused by water diffusion and condensation. The experiments revealed that, under Lithuanian climatic conditions, in the exploited building walls the sd value of the exterior layer of the thin render should make sd